Analysis of the Criminal Liability of Influencers from the Perspective of Criminal Law - I Gede Sadia Dwi Ratmaja (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
The development of information and communication technology has transformed product marketing from conventional media to digital marketing through social media platforms. In this context, influencers play a significant role in promoting products to the public. However, cases have emerged where influencers promote illegal products or products without proper distribution permits, potentially causing harm to consumers. The issues addressed in this study concern the legal regulation of product promotion through social media in Indonesia and the form of criminal liability of influencers who promote illegal products. This research employs a normative legal research method using statutory and conceptual approaches. Legal materials were collected through library research and analyzed qualitatively. The results show that product promotion through social media is subject to several legal provisions, including the Law on Electronic Information and Transactions, the Consumer Protection Law, and regulations concerning Electronic Commerce. Influencers may be held criminally liable if their promotional activities fulfill the elements of a criminal offense, particularly when there is an unlawful act, fault in the form of intent or negligence, and involvement in disseminating misleading information or facilitating the circulation of illegal products, which may be linked to the concept of participation under Articles 55 and 56 of the Criminal Code